Recovery and reuse of discontinuous carbon fibres by solvolysis: Realignment and properties of remanufactured materials - Oliveux, Géraldine; Bailleul, Jean-Luc; Gillet, Arnaud; Mantaux, Olivier; Leeke, Gary A. (Elsevier, 2016)
Discontinuous carbon fibre tows were recovered after solvolysis of an aeronautic type composite made with RTM6 epoxy resin. A Sohxlet extraction method was used to quantify the organic residue on the fibre tows and showed that less than 3 wt% was remaining on the surface. The recovered tows were therefore reused directly to manufacture a plate with randomly distributed carbon fibres and then three plates with realigned carbon fibres. The latter were then characterised and tested and the results obtained were compared to the material manufactured using the same type of virgin fibres by the same method. The materials made from recycled carbon fibres showed very good properties in comparison to the virgin fibre material, despite the presence of flaws such as quality of the fibre surface after solvolysis, alignment and voids). This is the first time in the open literature that carbon fibres recovered from solvolysis were reused in this way together with characterisation of the resulting materials.
Keywords: Carbon fibres; Discontinuous reinforcement; Recycling; Directional orientation